Estimation of yield loss in soybean triggered by Spodoptera litura: Estimation of yield loss in soybean triggered by Spodoptera litura - B SUNDAR; NANDA KHANDWE; M SURYA PRAKASH (Journal of Oilseeds Research, 2020)
Pest infestation has been identified as the major biotic factor limiting soybean yield worldwide. The current scenario of management mainly focuses on insecticides with a quick knockdown effect, not with host plant resistance techniques. The present work is for comparing both chemical and plant resistance. Fifty soybean genotypes with four replications (2 treated + 2 untreated) screened against Spodoptera litura infestation. Among them eleven varieties were resistant and high yielding (R-HY), seventeen were resistant and low yielding (R-LY) and twenty two varieties were susceptible and low yielding (S-LY). The grain yield range from 475.0 to 2375.0 kg/ha and 450.0 to 2263.0 kg/ha, in treated and untreated varieties, respectively. The grain yield loss ranged from 0.67 to 17.71 per cent in different varieties.